Upaya Dikyasa Terhadap Pengawasan Onderdil-Aksesoris Kendaraan Bermotor Di Kota Malang Prespektif Hukum Islam - maulana malik ibrahim (Journal of Islamic Business Law, 2018)
Regarding in auto parts-accessories of vehicles development. It often happened any problem when people used it on the road. In this case, this problem cannot be avoid when the people were driving on the road and made the weaknesses against another people that uses auto parts-accessories of vehicles with incompatible with allocation, then in this study more focused existing rules, but in the rules is still unresolved or less specific about the usability and functionality of auto parts-accessories of vehicles to the safety and security. Later in this study using a kind of empirical juridical research and also his approach to use the statute approach and conceptual approach, a location used for research at Polres DIKYASA kanit Malang and Dishub Batu city method of data collection by searching for the primary and secondary data then the dissemination by means of analysing. From the results in this study i.e. can be from any oversight conducted by THEN were in accordance with the Act No. 22 of year 2009, but in the presence of flaws in the law that makes all the violations committed by the society became problematic in the point Moreover, in the point of view of Islam, that problem can make a harm and it will take weaknesses to ourself or others.